A Review on Minutiae Extraction of Fingerprint - Rozita, Mohd Yusof; Norrozila, Sulaiman (SPROC LTD, 2013)
This paper discuss methods to identify minutiae or ridges consist of deciding whether the pixel evaluated belongs to same person or otherwise. A lot of researchers proposed an algorithm or a technique for the minutiae extraction. Normally, the minutiae such as ridge ending and bifurcation detection are based on segment neighboring ridges, directional of ridges block pixel. In this paper, a survey for describing minutiae detection has been conducted. This survey result is not only to identify similarities and differences of the approaches, but also to identify requiring further research.